The government policy’s influences on entrepreneurship and increasing micro industry income to reduce poverty - Rinawati, Herrukmi Septa (Management and Entrepreneurship: Trends of Development, 2019)
The existence of Micro, Small, and Medium enterprises in Indonesia is cannot be underestimated. Moreover, it has contributed to the growth of economy. The government, especially Regional Government has established several efforts in developing the influence of Regional Government’s policies on entrepreneurship. Thus, this research has purpose to know the influence of Regional Government’s policies on entrepreneurship to reduce poverty. Afterward, this research is conducted in two regions in Indonesia which are Pamekasan and Tulungagung. The research used mix method approach between qualitative and quantitative. The results show that the Regional Government put more emphasis on three things. First, capital assistance is considered important because the micro industry is more based on families whose capital is limited. Second, marketing assistance is expected to expand the market reach of the products produced. Capital assistance is carried out with various schemes. Third, the training assistance as well as the fourth assistance for Industrial and Trade (TPL) extension workers. Yet, it found that several assistances provided by the government are insignificant. Hence, the right strategy in developing small industries in Pemekasan and Tulungagung Regencies is to increase attention to policies in terms of capital assistance and capital assistance which still face many obstacles. The obstacles faced are the limited budget for increasing capital assistance and marketing assistance. The ease of access to business assistance sources and the opportunity to participate in product promotion exhibitions is less affected by entrepreneurs. The right strategy in developing small industries in regions under research is to increase attention to policies in terms of capital assistance which still face many obstacles.JEL Classification: D6, O4, Q0